Managing Safety Risks Associated with Nightshift in the New Zealand Electrical Distribution Industry - Sadgrove, Matthew (New Zealand Journal of Health and Safety Practice, 2025)
This study examines how the New Zealand electrical distribution industry approaches the management of fatigue-related impairment associated with night shift work. Using a qualitative study design, and reflexive thematic analysis, it draws on both industry-submitted documents and focus groups with Network Control Operators and Fault Responders to explore current practices, perceptions, and gaps in fatigue risk management. The research exposes a heavy reliance on the self-management of fatigue, ambiguous policies, and insufficient training. Findings ultimately highlight the need for defensible fatigue risk management strategies to safeguard workers and the public.